Comparison of Positive Affect in Used Indonesian Language and Foreign Language is Reviewed from Aspect of Social Support - Munira,; Thaba, Aziz (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to compare positive affect of language usage between Indonesian and foreign languages (English, German, and Arabic) in native speakers of the Indonesian language. This study uses a mixed method with the number of respondents as many as 150 people. Data were collected by questionnaire and interview techniques, then analyzed with concurrent embedded strategy. The results of this study were (1) social support for native speakers of Indonesian in using low Indonesian language (only 50.95%) so that the positive affect of native Indonesian speakers on the use of Indonesian language was low (only 49.95%); (2) social support for native speakers of the Indonesian language in the use of foreign languages high (70.93%) so that the positive affect of native speakers of Indonesian against the use of foreign languages was high (77.96%); And (3) The high positive affect on the use of foreign languages in native speakers of Indonesia is due to the acquisition of high confidence, prestige, and social security in the future.